(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
Several patients experience at least one drug-related problem and Pharmaceutical Care can change this reality. This work describes a model for structuring the pharmaceutical care service at a pharmacy training unit of the Brazilian Public Health System based on pharmacotherapy follow-up program of Parkinson’s disease patients’ results. From the follow-up results (phase 1), a Therapy Management Scheme was designed (phase 2). Of the 57 patients followed-up, 30 presented at least one drug-related problem and 42% were non-adherent to treatment, which supported the need of pharmacotherapy management. The Pharmacotherapy Management Scheme was proposed as a pharmaceutical care service model, which presents 6 steps: first, the pharmacist fills out the dispensing form and assesses patient´s pharmacotherapy, if there is a suspect problem, he is invited to the follow-up (steps 1 and 2) and they agree the first appointment. After that, pharmacist studies the patient’s case (study phase, steps 3 and 4). At the second meeting, the pharmacist proposes the intervention needed, and at the third, assesses the intervention results and new problems (steps 5 and 6, respectively). The process ends when all therapeutics outcomes are reached. This practical model can significantly contributed to the development and organization of pharmaceutical care services.